NO and N2O accumulation during nitrite-based sulfide-oxidizing autotrophic denitrification. (September 2019) - Lan, Lan; Zhao, Jianqiang; Wang, Sha; Li, Xiaoling; Qiu, Liping; Liu, Shuang; Bin Nasry, Allma Al Naim
Abstract: A series of batch tests were carried out in a nitrite-based Sulfide-oxidizing autotrophic denitrification (SOAD) lab-scale sequencing biofilm batch reactor under four different influent conditions. Results indicated that the two stages of sulfide oxidized to S 0 and S 0 oxidized to SO4 2− proceed successively and could be distinguished by pH variation. The dissolved nitrous oxide (N2 O) and nitric oxide (NO) monitored online were observed accumulating at the beginning of every new cycle once nitrite and sulfide were fed in pulse. Along with the NO accumulation dissolved oxygen (DO) level increased, accidentally, although the reactor was sealed and no aeration. The high nitrite concentration caused the NO accumulation which could be promoted by the low ratio of S/N. N2 O accumulation resulted from the double inhibitions of sulfide and FNA. Thiobacillus, Ottowia, Thiovirga presented the functional genera to remove sulfide and nitrite in this study. Highlights: High NO and N2 O accumulation were observed during nitrite-based SOAD. NO dismutation may occur along with the NO accumulation. NO accumulation was attributed to the high rate of nitrite reduction. N2 O accumulation resulted from the double inhibitions of sulfide and FNA.